The winner`s curse: Behavioral economics enomalies, then and now - Thaler, Richard H.; Imas, Alex O. (United Kingdom Penguin Books, 2025)
Nobel Prize-winner and co-author of Nudge, Richard Thaler, and rising star economist Alex Imas explore behavioral economics in this fully updated edition of the seminal work The Winner$1 (Bs Curse Why do people cooperate with one another when they have no incentive to do so? Why do we hold onto possessions of little value? And why is the winner of an auction so often disappointed.s